(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article analyzes the current state of the transport sector of the economy, emphasizing the important role of transport as the lifeblood of the national economy, the development of which leads to the growth of other sectors that meet the needs of the country’s population. Along with some positive indicators, the existing shortcomings of the industry are noted, and recommendations are given.